Genetic diversity in tef [Eragrostis tef (Zucc.) Trotter] - Assefa, Kebebew; Cannarozzi, Gina; Girma, Dejene; Kamies, Rizqah; Chanyalew, Solomon; Plaza-Wüthrich, Sonia; Blösch, Regula; Rindisbacher, Abiel; Rafudeen, Suhail; Tadele, Zerihun (Frontiers in Plant Science, 2015)
Tef [Eragrostis tef (Zucc.) Trotter] is a cereal crop resilient to adverse climatic and soil conditions, and possessing desirable storage properties. Although tef provides high quality food and grows under marginal conditions unsuitable for other cereals, it is considered to be an orphan crop because it has benefited little from genetic improvement. Hence, unlike other cereals such as maize and wheat, the productivity of tef is extremely low. In spite of the low productivity, tef is widely cultivated by over six million small-scale farmers in Ethiopia where it is annually grown on more than three million hectares of land, accounting for over 30% of the total cereal acreage. Tef, a tetraploid with 40 chromosomes (2n=4x=40), belongs to the Family Poaceae and, together with finger millet (Eleusine coracana Gaertn), to the Subfamily Chloridoideae. It was believed to have originated in Ethiopia. There are about 350 Eragrostis species of which E. tef is the only species cultivated for human consumption. At the present time, the gene bank in Ethiopia holds over five thousand tef accessions collected from geographical regions diverse in terms of climate and elevation. These germplasm accessions appear to have huge variability with regard to key agronomic and nutritional traits. In order to properly utilize the variability in developing new tef cultivars, various techniques have been implemented to catalog the extent and unravel the patterns of genetic diversity. In this review, we show some recent initiatives investigating the diversity of tef using genomics, transcriptomics and proteomics and discuss the prospect of these efforts in providing molecular resources that can aid modern tef breeding.